2016
DOI: 10.1093/eurpub/ckw053
|View full text |Cite|
|
Sign up to set email alerts
|

Does unemployment cause long-term mortality? Selection and causation after the 1992–96 deep Swedish recession

Abstract: Background: Mass unemployment in Europe is endemic, especially among the young. Does it cause mortality? Methods: We analyzed long-term effects of unemployment occurring during the deep Swedish recession 1992–96. Mortality from all and selected causes was examined in the 6-year period after the recession among those employed in 1990 (3.4 million). Direct health selection was analyzed as risk of unemployment by prior medical history based on all hospitalizations 1981–91. Unemployment effects on mortality were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 29 publications
7
48
0
1
Order By: Relevance
“…However, the predominance of flows between employment categories towards non-employment during the crisis may also have contributed to the unfavourable change. Our findings are consistent with previous studies indicating a positive association during the crisis between unemployment and alcohol-related mortality,12 20 21 25 or problem drinking14 22–24 and with a Spanish study indicating an increased frequency of alcohol-related disorders in primary healthcare during 2006–2010, and a stronger positive association between such disorders and unemployment in 2010 13. However, another Spanish study showed no heterogeneous changes in heavy or binge drinking prevalence by employment status during the crisis 15.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the predominance of flows between employment categories towards non-employment during the crisis may also have contributed to the unfavourable change. Our findings are consistent with previous studies indicating a positive association during the crisis between unemployment and alcohol-related mortality,12 20 21 25 or problem drinking14 22–24 and with a Spanish study indicating an increased frequency of alcohol-related disorders in primary healthcare during 2006–2010, and a stronger positive association between such disorders and unemployment in 2010 13. However, another Spanish study showed no heterogeneous changes in heavy or binge drinking prevalence by employment status during the crisis 15.…”
Section: Discussionsupporting
confidence: 93%
“…A higher sensitivity of DAA mortality to cyclical variation in economic conditions at younger ages is plausible, given the greater financial insecurity of young people 4. Finally, among employees, our study suggests more favourable crisis effects on the outcome in married than unmarried people, which is also consistent with previous studies 14 25 26…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…But for whom are these consequences most apparent? While men may be more disadvantaged in terms of increased mortality risk following unemployment,3 we find that patterns related to social mobility portray a different image. Older women are at the greatest disadvantage; they have high odds of mortality if downwardly mobile, but reap none of the benefits of upward mobility.…”
Section: Discussionmentioning
confidence: 56%